Comparative Analysis of Energy Efficiency Measurement in Building with Manual Calculation and RETScreen Expert - Saputra, Andika; Kurniawan, Andre; Fernanda, Yolli; Karudin, Arwizet; Ahmed, Shabir (Universitas Negeri Padang, 2024)
Energy efficiency is a crucial aspect of energy saving efforts. Energy efficiency is an important factor in reducing energy consumption and environmental impacts. One of the important steps that can be taken in achieving energy efficiency is to conduct an energy audit. An energy audit is a systematic process to evaluate energy use in a building and identify energy saving opportunities that can be done. RETSCreen Expert is one of the software that can be used for energy audits. This research focuses on analyzing the comparison between manual calculations and calculations using RETScreen Expert software on building energy efficiency. The factors used to analyze energy efficiency are air conditioning systems, room lighting systems, and the use of other electronic devices, over a one-year period. The analysis results show that there are differences in calculations between the use of manual methods and RETScreen Expert. The difference between manual calculation and RETScreen Expert is 15.42%. With this difference, it is assumed that manual calculations and calculations using RETScreen Expert do not have too much difference. The results of the energy audit also show that the air conditioning system (HVAC) is a major contributor to the building's energy consumption.